PENGARUH KONSERVATISME AKUNTANSI DAN INTENSITAS MODAL TERHADAP TAX AVOIDANCE DENGAN DEWAN KOMISARIS INDEPENDEN SEBAGAI VARIABEL MODERATING - Nurul Alfian (JURNAL AKUNTANSI DAN INVESTASI, 2022)
This study aims to provide empirical evidence that accounting conservatism and capital intensity affect tax avoidance, as well as the existence of an independent board of commissioners as a moderating variable to interact with the relationship between accounting conservatism and capital intensity on tax avoidance. This research is associative, sample selection is done by purposive sampling method. The data used are secondary data and annual reports, while the data analysis techniques used are descriptive statistical analysis and multiple regression analysis and for statistical analysis of moderating variables using the value test using SPSS 21.The results of this study indicate that accounting conservatism has a significant negative effect on tax avoidance, while capital intensity has a significant and positive effect on tax avoidance. And the independent board of commissioners is able to moderate the effect of accounting conservatism on tax avoidance, while the independent board of commissioners is not a variable that moderates the effect of capital intensity on tax avoidance.